Validation of Cognitive-based Mindfulness Program to Reduce Suicidal Ideation in Individuals with Depression - Ainurizan Ridho Rahmatulloh; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Suicide is a global epidemic phenomenon that is the third most common cause of death in the world. However, not many studies have focused on developing an intervention that specifically targets symptoms of suicidal ideation. Suicidal ideation is seen as part of a depressed condition. The purpose of this study was to validate a cognitive-based mindfulness program to reduce suicidal ideation in people with depression. The study was conducted through internal validity tests using expert judgment and external validity tests using the small-n AB design method, which involved three participants (n = 3). The visual inspection analysis was performed on the mean, trend, and level. Analysis of repeated measurements showed adecrease in suicidal ideation in all participants. This program has the potential to be developed as a companion to conventional interventions and can be an alternate activity to fill the waiting time for individuals to get the main intervention